Creación de productos educomunicativos para alfabetidad patrimonial en la provincia de El Oro - Jaén Ortega, Marlon Fabricio (Machala, 2020)
In the interior of the province of El Oro, information related to cultural heritage issues is very scarce, the panorama surrounding cultural heritage has been uncertain and in the absence of cultural promotion, on several occasions people have been at risk of forgetting that ancestral knowledge that has been transmitted from generation to generation; even so, a sector of society has taken the initiative to care for that legacy left by our ancestors, if this were to increase the individual can intuitively analyze what is the true reality and the danger facing cultural heritage. Currently, the lack of work that keeps alive traditions and knowledge, allow current generations to know little or nothing of the legacy of their parents, the classification of heritage in two major groups comes to make a stumbling block for itself, according to Fontal (2017) does not give relevant attention to intangible heritage as these are the legacies of history that are most likely to be forgotten and can leave humanity a space that can not be filled so easily, irremediably damaging human culture. For this reason within this investigation we propose the creation of audiovisual products which can in some way create expectations with different audiences, in this case was directed to a group of children in the city of Santa Rosa, within which they verified that the correct use of this type of product with a good story can engage the desired audience and thus make the user can consume the content in its entirety. Within the new era, the interaction of the media with the citizens has caused a growing wave of information, due to this the use of different resources and educomunicative products such as videos and their genres, have been helpful for the distribution of different contents whether they are entertainment or educomunicative; for this reason they have become an indispensable tool within companies, projects or enterprises; Its easy handling and adaptability, allows the user to divide in an appropriate way each of the products to be used and put them within a base structure and thus segment the audiences, their environment and the area of performance of each of these; In this case, the confrontation of different theories allowed us to get the best out of each of these audiovisual products, which allows us to deal with educational issues such as cultural heritage, among others, while applying methodologies that involve the target audience and the different media, whether traditional or digital, resulting in a decrease in misinformation regarding cultural heritage issues. Throughout this investigation it has been verified that the correct application of this resource, allows the perfect performance of each one of the products used within its surroundings demonstrating its efficiency accompanied by a methodology that supports it when we speak of educational subjects; the use and the application of the different methodologies of the investigation have allowed to give a solid base for this investigation turning it into an investigation-action which allows the carrier to facilitate the direction and to avoid the dispersion of the main idea giving like result a correct optimization of the wished results.
Al interior de la provincia de El Oro, la información relacionada a temas de patrimonio cultural es muy escasa, el panorama que rodea al patrimonio cultural ha sido incierto y al no existir el fomento de la cultura, en varias ocasiones las personas han estado en riesgo de olvidar aquellos conocimientos ancestrales que han sido transmitidos de generación en generación; aun así, un sector de la sociedad ha tomado la iniciativa de cuidar aquel legado que han dejado nuestros ancestros, si esto incrementara el individuo puede analizar de manera intuitiva, cuál es la verdadera realidad y el peligro que enfrenta el patrimonio cultural. Actualmente, la falta de un trabajo que mantenga vivas las tradiciones y conocimientos, permiten a las generaciones actuales saber muy poco o nada del legado de sus padres; la clasificación del patrimonio en dos grandes grupos llega a hacer una piedra de tropiezo para sí mismo, según Fontal (2017) no se le da la atención pertinente al patrimonio intangible ya que estos son los legados de la historia que más riesgo corren de ser olvidados y pueden dejar a la humanidad un espacio que no puede ser llenado tan fácilmente; perjudicando irremediablemente a la cultura humana. Por tal motivo dentro de esta investigación proponemos la creación de producto audiovisuales los cuales pueden en cierto modo crear expectativa con los diferentes públicos, en este caso fue direccionado a un grupo de niños de la ciudad de Santa Rosa, dentro de los cuales verificaron que el correcto uso de este tipo de productos con una buena historia puede enganchar al publico deseado y de esta manera hacer que el usuario pueda consumir el contendió en su totalidad. Dentro de la nueva era, la interacción de los medios con la ciudadanía ha provocado una creciente ola de información, debido a esto la utilización de distintos recursos y productos educomunicativos como los videos y sus géneros, han sido de ayuda para la distribución de los diferentes contenidos ya sean estos de entretenimiento o educomunicativos; por tal motivo se han vuelto una herramienta indispensable dentro de empresas, proyectos o emprendimientos; su fácil manejo y adaptabilidad, permite a quien lo use, dividir de una manera adecuada cada uno de los productos a utilizar y ponerlos dentro de una estructura base y de esta manera segmentar los públicos, su entorno y el área de desempeño de cada uno de estos; en este caso la confrontación de diferentes teorías permitió sacar lo mejor de cada uno de estos productos audiovisuales, lo que permite tratar temas educativos como el patrimonio cultural, entre otros al mismo tiempo aplicar metodologías que involucren al público objetivo y los diferentes medios de comunicación ya sean estos tradicionales o digitales dando como resultado la disminución de la desinformación en cuanto a temas de patrimonio cultural. A lo largo de esta investigación se ha ido verificando que la correcta aplicación de este recurso, permite el perfecto desempeño de cada uno de los productos utilizados dentro de su entorno demostrando su eficiencia acompañado de una metodología que lo respalde cuando hablamos de temas educativos; la utilización y la aplicación de las diferentes metodologías de la investigación han permitido dar una base sólida para esta investigación convirtiéndola en una investigación-acción lo que permite al portador facilitar la dirección y evitar la dispersión de la idea principal dando como resultado una correcta optimización de los resultados deseados.
Keywords: EDUCOMUNICACION; ALFABETIDAD PATRIMONIAL; INVESTIGACION-ACCION; PRODUCCION AUDIOVISUAL